High‐mobility group box‐1 (HMGB‐1) and serum soluble receptor for advanced glycation end products (sRAGE) in children affected by vernal keratoconjunctivitis. Issue 1 (17th November 2013) - Zicari, Anna Maria; Zicari, Alessandra; Nebbioso, Marcella; Mari, Emanuela; Celani, Camilla; Lollobrigida, Valeria; Marcelli, Azzurra Cesoni; Occasi, Francesca; Duse, Marzia
Abstract Background Vernal keratoconjunctivitis (VKC) is a chronic disease affecting conjunctiva even though the immunopathogenetic mechanisms underlying this inflammation are unclear. The aim of our study is to investigate serum levels of HMGB1 and circulating sRAGE in children affected by VKC before and after treatment with cyclosporine A (CsA) eye drops and in a group of healthy children. Methods Twenty‐four children affected by VKC aged between 5 and 12 yrs of life were enrolled at the Department of Pediatrics, Division of Allergy and Immunology, 'Sapienza' University of Rome. Twenty‐four healthy children without atopy, ocular, and systemic disease, cross‐matched for sex and age to patients affected by VKC, represented the controls. All children affected by VKC were treated with CsA 1% eye drops for 4 wks, and blood samples were collected before and 2 wks after the end of treatment while the controls underwent to a single blood sample at the time of enrollment. Results Serum basal levels of HMGB1 and sRAGE were higher in children with VKC when compared with controls while, in patients affected by VKC, no difference was detected between atopic and non‐atopic, and between ANA‐positive and ANA‐negative children. A significant reduction in serum HMGB1 and sRAGE levels was detected after the therapy while CsA serum levels were negative. Conclusions Our study gives a support to the definition of VKC as a systemic inflammation in which HMGB1 and its soluble receptors could play a role.